Sosialisasi Memilah Sampah Menjadi Ecobrik Kepada Ibu PKK Dinagari Sumanik Kecamatan Salimpaung Kabupaten Tanah Tadar - Rahmaita; Annisa Mardhatillah; Aura Salsabila; Adinda Denada; Muhammad Rafli; Yandi Ramadhani (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Sumanik is one of the nagari located in Silimpaung District, Tanah Datar Regency, known for its lush environment and cool air. This natural beauty must be preserved to prevent pollution caused by the increasing amount of household waste, especially plastic waste. As an effort to maintain cleanliness and environmental sustainability, a socialization program on waste separation and its utilization into ecobricks (eco-friendly bricks) was conducted with the PKK women of Nagari Sumanik. This activity aims to raise public awareness, particularly among women, about the importance of managing household waste wisely and creatively. Through this training, the women were taught how to separate waste, compress plastic into bottles, and use ecobricks as simple building materials. It is hoped that this activity will foster new environmentally friendly habits and position Nagari Sumanik as a role model for waste management awareness.